Effect of Nigella sativa L. extract on improving memory function through reducing GSK3β activation and Aβ42/40 ratio - Kusuma Andriana; Nurdiana; Wisnu Barlianto; I Wayan Arsana Wiyasa; Masruroh Rahayu (GarVal Editorial Ltda., 2022)
Context: Alzheimer's disease (AD) is one of the biggest causes of public health problems today, especially in older, where women have a greater risk of developing AD than men. However, the current AD therapy has not been satisfactory. Nigella sativa(NS) has bioactive compounds of flavonoid compounds and estrogenic effects that could be alternative medicine. Aims: To evaluate an extract of N. sativa on improving memory function through reducing GSK3β activation and Aβ42/40 ratio in a model of AD in rats. Methods: This research was an experimental study with the post-test-only group design using 24 Wistar rats divided into eight groups. Conjugated equine estrogen (CEE) 0.018-0.0036 mg/day and NS 100, 200, and 400 mg/kg BW were administered orally two weeks before intraperitoneal AlCl3 induction, then continued for up to 8 weeks. In the last five days of the study, the Morris water maze memory test was performed to analyze the expression of amyloid β (Ab), neurofibrillary tangles (NFT), glycogen synthase kinase 3β (GSK3β), and Aβ42/40 ratio. Results: There were significant differences in the memory test (p = 0.000), the expression Aβ40 (p = 0.000), Aβ42 (p = 0.000), NFT (p = 0.000) and GSK3β levels (p = 0.000). The lowest expression of Aβ40 in the NS100 group, Aβ42 in the NS400, NFT in the CEE group, and GSK3β levels in the NS100 group. Administration of NS increased the plasma ratio of Ab42/40 with the highest mean in the CEE group (p = 0.001). Conclusions: The administration of NS extract affected improving memory function by decreasing the expression of Aβ, NFT, GSK3β in ovariectomized Wistar rats supplemented with AlCl3.